Etnomatematika pada Alat Musik Tradisional Kendang dalam Kesenian Gamelan Jawa dengan Mengaitkan Konsep Matematika - Fajarianty, Maria Meilany; Pramudita, Anastasia Farren; Ningrum, Marcelia Puspita (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Indonesia is a country that has cultural diversity. Each region in Indonesia from Sabang to Merauke has its own cultural characteristics according to the situation and conditions in that region, such as the natural environment, customs, history to the character of the people in that region. Culture is one of the right tools to elevate the characteristics of society, nation and state. Ethnomatematics as a bridge between culture and mathematics that can provide knowledge related to habits that are inherent in local traditions in mathematics material. In this regard, researchers will develop ethnomathematics with cultural elements. This study presents the results of an exploration of ethnomathematics forms that can be found in Javanese gamelan art in the form of the traditional drum musical instrument. This research is a qualitative exploratory research using an ethnographic approach. Data collection techniques used interview techniques with sources online and used literature study techniques which were carried out by means of literature study. The result of this research is that the mathematical concept of the physical form of the drum instrument is found, which is in the form of a truncated conical curved side chamber because it has a different base and roof size. In addition, the mathematical concept found is regarding integrals which can be used to calculate the area of the drum covers using the help of the Geogebra aplication